2010
DOI: 10.1074/jbc.m110.122523
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Substrate-binding Site in the Homodimeric Mannitol Transporter, EIImtl, of Escherichia coli

Abstract: The mannitol transporter from Escherichia coli, EII mtl , belongs to a class of membrane proteins coupling the transport of substrates with their chemical modification. EII mtl is functional as a homodimer, and it harbors one high affinity mannitol-binding site in the membrane-embedded C domain (IIC mtl remains the same. We conclude that during the transport cycle, the phosphorylated B domain has to move to the mannitol-binding site, located in the middle of the membrane, to phosphorylate mannitol.Membrane-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…9a), the C6-OH would be accessible for phosphorylation. This orientation would also place the C6-OH within hydrogen-bonding distance of the conserved residues Glu334 and His250, whose importance for sugar binding and phosphorylation has been demonstrated in an EIIC that transports mannitol 16,17,3234 . In contrast, the alternate orientation would position the C6-OH in the protein interior (Supplementary Fig.…”
Section: Substrate Binding Sitementioning
confidence: 99%
“…9a), the C6-OH would be accessible for phosphorylation. This orientation would also place the C6-OH within hydrogen-bonding distance of the conserved residues Glu334 and His250, whose importance for sugar binding and phosphorylation has been demonstrated in an EIIC that transports mannitol 16,17,3234 . In contrast, the alternate orientation would position the C6-OH in the protein interior (Supplementary Fig.…”
Section: Substrate Binding Sitementioning
confidence: 99%
“…Endogenous bound ligand has also been reported for PtsG[68]. The discovery that the mannitol binding site was positioned asymmetrically within the MtlA dimer led to the further hypothesis that the protomers acted in an alternating fashion, with passage of mannitol through one protomer causing it to switch from high affinity to low affinity and consequently driving the other protomer from a low affinity to a high affinity state capable of binding ligand [69]. This differs from what was observed in the bcChbC crystal structure in which the sugar molecule was bound to both protomers in a symmetric fashion.…”
Section: Transportmentioning
confidence: 99%
“…There is currently no evidence of cooperativity in the bcChbC dimer; however, given that the cytoplasmic gate appears to be supplied by the opposing protomer, it is possible that this could provide a mechanism for cooperativity, as sugar exiting the cavity of one protomer could be sensed by the other. Furthermore, residues in the N-terminal half of MtlA (the region corresponding from TM1 to TM4 in bcCHBC) were shown to be in close contact with mannitol, the sugar was shown to be located closer to the periplasm, and substantial differences were observed between solvent exposed residues in MtlA and their expected counterparts in the bcChbc structure[69, 70]. Tryptophan phosphorescence spectroscopy indicated that F97 in MtlA (a predicted cytoplasmic loop residue that overlays TM3 in bcChbC) is part of a β-sheet fold[71].…”
Section: Transportmentioning
confidence: 99%
“…This interaction seems to occur only with unphosphorylated EIIB Mtl , because first, the Cys-Asp replacement in EIIB Mtl prevented the interaction with MtlR in yeast-two hybrid experiments (146) and second, replacement of the phosphorylatable Cys with a Ser in soluble EIIB Mtl prevented the inhibitory effect on PmtlA expression observed with wild-type EIIB Mtl (71). In contrast to cysteyl-phosphorylated EIIB Mtl , seryl-phosphorylated EIIB Mtl cannot transfer its phosphoryl group to mannitol (148) and, owing to the lowenergy phosphate bond, probably cannot pass it back to EIIB Mtl . As a consequence, P-Ser-EIIB Mtl accumulates in the cytoplasm, and the phosphorylated mutant EIIB Mtl apparently no longer competes with the EIIB Mtl domain of MtlA for binding MtlR and rendering it inactive (71).…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%